‘Social Re-presentation for…’: An Action-Oriented Formula for Intergroup Relations Research - Buhagiar, Luke J.; Sammut, Gordon (Frontiers in Psychology, 2020)
Intergroup relations are of crucial importance in contemporary times, with concerns around social representations, social influence and collective action remaining salient. A core aspect of intergroup conflict revolves around the notion of joint projects, whereby different collectives seek to promote their own project through processes of joint intentionality. Nonetheless, we contend that intergroup relations research can tackle the notion of projects more fruitfully by studying the mutual understandings of projects of groups in conflict. Accordingly, we propose an action-oriented reformulation for intergroup relations research, which is contrasted with the standard object-oriented formula. Object-oriented research either (a) emphasizes the study of social objects without regard for their different construal by members of conflicting groups, or (b) focuses on ‘social representations of’ the objects in question, without regard for the projects that such representations serve. Contrastingly, action-oriented research (a) seeks to understand a collective’s ‘social re-presentation for’ a specific project; and (b) studies the social and alternative re-presentation of objects and projects as a systemic product of intergroup relations. We then present illustrative examples of object-oriented research, followed by a study concerning Arab-Maltese relations in Malta as an example of action-oriented research. We end by making recommendations for future research on intergroup relations, with the aim of shedding light on the processes that bind coalitions for collective action.